The Use of Language by the Siamese Community and Its Influences on Cultural Integration: A Case Study in Kampung Keluang, Besut, Terengganu - Wan Nor Jazmina, Wan Ariffin; Ramle, Abdullah (2018)
This study is conducted to observe how language element gives impact to the integration of the Siamese and Malay communities in Kampung Keluang. The study is done by applying two techniques of data collection through fieldwork, namely join observation and thematic interview with the villagers in Kampung Keluang which consist of the Malays and Siamese, besides some other noteworthy individuals. The research findings showed the Siamese community use Malay language as their main language in daily undertakings and their fluency in in using the language has become an element that fosters their integration with the surrounding Malay community. Nevertheless, Siamese language is kept preserved as an identity of the Siamese through informal approach such as the socialization of parents towards their children. Preservation of the Siamese identity through their mother-tongue apparently has not given any repercussion towards integration process of the society in Kampung Keluang. The sharing of language with similar dialect, with the Malay community by the Siamese community proved that they have shared a comparable code system when interacting and it has given positive impact to the social integration in Kampung Keluang.